The pharmacology and therapeutic role of cannabidiol in diabetes - Jin Zhang; Cong Lin; Sha Jin; Hongshuang Wang; Yibo Wang; Xiubo Du; Mark R. Hutchinson; Huiying Zhao; Le Fang; Xiaohui Wang (Exploration, 2023)
Abstract In recent years, cannabidiol (CBD), a non‐psychotropic cannabinoid, has garnered substantial interest in drug development due to its broad pharmacological activity and multi‐target effects. Diabetes is a chronic metabolic disease that can damage multiple organs in the body, leading to the development of complications such as abnormal kidney function, vision loss, neuropathy, and cardiovascular disease. CBD has demonstrated significant therapeutic potential in treating diabetes mellitus and its complications owing to its various pharmacological effects. This work summarizes the role of CBD in diabetes and its impact on complications such as cardiovascular dysfunction, nephropathy, retinopathy, and neuropathy. Strategies for discovering molecular targets for CBD in the treatment of diabetes and its complications are also proposed. Moreover, ways to optimize the structure of CBD based on known targets to generate new CBD analogues are explored.